First report and evidence of multiple origins of diflubenzuron resistance alleles in Culex pipiens mosquito from Cyprus - Valentina Mastrantonio; Marlen Vasquez; Gregoris Notarides; Eleni Patsoula; Valentina Lucchesi; Flavio Piras; Romeo Bellini; Daniele Porretta (Parasites & Vectors)
Abstract Background Insecticide resistance is one of the primary problems affecting vector control worldwide. Assessing the occurrence of resistant alleles and understanding their origin across the geographic range of vector species is crucial for effective resistance management. In populations of the mosquito Culex pipiens, point mutations conferring resistance to the insecticide diflubenzuron (DFB) were recently found across the Mediterranean basin. In this study, we investigated the possible occurrence of DFB resistance in Cyprus, where West Nile virus outbreaks have been documented in recent years. Methods We sequenced a fragment of the chitin-synthase 1 gene carrying the resistant mutations in individuals collected from 18 populations of Cx. pipiens in Cyprus to investigate the occurrence of DFB-resistant alleles. We then assessed the evolutionary origin of DFB-resistant alleles by reconstructing the phylogenetic relationships between susceptible and resistant alleles found across the Mediterranean basin. Results Our screening revealed the occurrence of the I1043F allele in all the districts analyzed. Notably, a new gene codon underlying the I1043F allele was detected. To our knowledge, this has not been previously reported in areas with DFB-resistance alleles in Cx. pipiens. In addition, we observed that the I1043F alleles detected in Cyprus have a different genetic background from those reported in other geographic areas, such as Italy and Turkey. Conclusions To our knowledge, this is the first time in which DFB resistance was revealed in Cx. pipiens populations occurring in Cyprus. Furthermore, we demonstrate that I1043F-resistant alleles have an independent origin in Cyprus, further supporting the hypothesis of a multiple independent origin of DFB resistance across the Mediterranean region. These results stress the need for regular resistance surveillance activities and the urgency of developing new mosquito control strategies. Graphical abstract